Impact of the Anatomical Localization of the Exit Site on Complications in Patients on Peritoneal Dialysis - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; TUĞLULAR, ZÜBEYDE SERHAN (AVES, 2021)
Background: Infections are the most common complications in patients with peritoneal dialysis (PD). The association between the anatomical localization of the exit site (ES) and infectious complications is unclear. In this study, we evaluated the relationship between the anatomic location of the ES and infectious complications of PD. Methods: We examined the ES of 53 patients on PD. To define the anatomical localization of the ES, its distance from the line between right and left anterior superior iliac spines (A line), umbilicus (B line), and the anterior superior iliac spine on the catheter side (C line) was measured. Results: Coiled catheters were used in all patients. The mean lengths of A line, B line, and C line were 4.1 +/- 2.2 cm (range, 0-9.5 cm), 9.6 +/- 2.9 cm (range, 4-17 cm), and 9.3 +/- 2.9 cm (range, 5-18 cm), respectively. ES infection was documented in 9 patients (17%), tunnel infection in 1 patient (2%), and peritonitis in 27 (50.9%) patients. The B line was significantly longer in those with peritonitis than those without peritonitis (10.6 +/- 3 vs. 8.7 +/- 2.7 cm; P = .036). Other variables were not associated with infectious complications. Conclusion: There was an association between the anatomical localization of the ES and the development of peritonitis. An ES close to the umbilicus could reduce the risk of peritonitis by enabling access by the patient to perform daily care.
Keywords: Exit-site; peritonitis; peritoneal dialysis